2018
DOI: 10.1016/j.neuroscience.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Kainate Receptors Play a Role in Modulating Synaptic Transmission in the Olfactory Bulb

Abstract: Glutamate is the neurotransmitter used at most excitatory synapses in the mammalian brain, including those in the olfactory bulb (OB). There, ionotropic glutamate receptors including N-methyl-d-aspartate receptors (NMDARs) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) play a role in processes such as reciprocal inhibition and glomerular synchronization. Kainate receptors (KARs) represent another type of ionotropic glutamate receptor, which are composed of five (GluK1-GluK5) subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 163 publications
(434 reference statements)
2
23
0
Order By: Relevance
“…The methods for preparing primary cultures of OB neurons have been previously described (Trombley and Blakemore, 1999;Blakemore et al, 2006;Blakemore et al, 2018). Briefly, the OBs were dissected from male and female postnatal days 0-4 (P0 to P4) Sprague-Dawley rat pups (Charles River, Wilmington, MA, USA), stripped of their meninges, cut into small pieces, and incubated for 1 hr at 37° C in a calcium-buffered papain solution (Worthington Biochemical, Lakewood, NJ, USA).…”
Section: Tissue Culturementioning
confidence: 99%
See 2 more Smart Citations
“…The methods for preparing primary cultures of OB neurons have been previously described (Trombley and Blakemore, 1999;Blakemore et al, 2006;Blakemore et al, 2018). Briefly, the OBs were dissected from male and female postnatal days 0-4 (P0 to P4) Sprague-Dawley rat pups (Charles River, Wilmington, MA, USA), stripped of their meninges, cut into small pieces, and incubated for 1 hr at 37° C in a calcium-buffered papain solution (Worthington Biochemical, Lakewood, NJ, USA).…”
Section: Tissue Culturementioning
confidence: 99%
“…We used our previous morphological criteria (Trombley and Westbrook, 1990), which correspond well with our prior immunocytochemical/cell marker criteria (i.e., VGLUT1, GAD) (Blakemore et al, 2018), to identify presumptive M/T cells and interneurons in OB cultures. M/T cells were identified based on soma size (20 to 40 μm) and shape (pyramidal, multipolar) and were differentiated from the larger population of small-diameter (5-10 μm) interneurons based on soma size.…”
Section: Neuronal Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…We subsequently showed that KAR activation increases the frequency of excitatory spontaneous activity in OB interneurons, possibly by depolarizing mitral/tufted (M/T) cells closer to their threshold for spiking and enhancing glutamate release (Davila et al, 2007). Recently, we used combinations of KAR agonists and AMPAR antagonists to explore the distribution and circuit functions of KARs in the OB (Blakemore et al, 2018). Our findings suggest that a variety of OB neuron subtypes express functional KARs, which modulate excitatory and inhibitory transmission.…”
Section: Introductionmentioning
confidence: 81%
“…Sensory information is first processed in the main and accessory olfactory bulb via various neurotransmitters, either supplied directly by local interneurons of both, the main and accessory olfactory bulbs (main olfactory bulb: Murphy et al, 2004;Shepherd, 2004;Ennis et al, 2007;Linster and Cleland, 2016;Blakemore et al, 2018;Dong and Ennis, 2018; accessory olfactory bulb: Brennan et al, 1995;Dudley and Moss, 1995;Jia et al, 1999;Mohrhardt et al, 2018), via the horizontal limb of the diagonal band (GABAergic and cholinergic input; Brashear et al, 1986;Zaborszky et al, 1986) and the locus coeruleus (noradrenergic input; McLean et al, 1989). Several studies focused on the role of neurotransmitters in the olfactory system and showed that AMPARs/kainateRs and NMDARs regulate the excitability of mitral and tufted cells (Salin et al, 2001;Urban and Sakmann, 2002;Christie and Westbrook, 2006;Blakemore et al, 2018). Further, glutamatergic receptors play a role in vomeronasal stimulation in the glomeruli of the accessory olfactory bulb, enabling social and reproductive events (Dudley and Moss, 1995;Mohrhardt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%